2013
DOI: 10.1002/jsfa.6270
|View full text |Cite
|
Sign up to set email alerts
|

Yacare caiman (Caiman yacare ) trim hamburger and sausage subjected to different smoking techniques

Abstract: For all the products, the hot smoking resulted in the lowest acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
4
6
0
2
Order By: Relevance
“…Similar results were reported for different yacare sausage treatments (Fernandes et al, 2013). However, that study revealed significant decreases in some sensory attributes of hot smoked sausages due to excessive dehydration and the highest salt concentration (Fernandes et al, 2013).…”
Section: Microbiological Analyses T1 T2 T3supporting
confidence: 84%
See 1 more Smart Citation
“…Similar results were reported for different yacare sausage treatments (Fernandes et al, 2013). However, that study revealed significant decreases in some sensory attributes of hot smoked sausages due to excessive dehydration and the highest salt concentration (Fernandes et al, 2013).…”
Section: Microbiological Analyses T1 T2 T3supporting
confidence: 84%
“…Thus, the high ash contents of the sausages (Table 2) could be explained by the addition of condiments and salts with inorganic residues (Nascimento et al, 2007;Cavenaghi-Altemio et al, 2013), which did not vary for the different formulations. In accordance with this, literature reports ash contents of 3.92 and 8.21% for unsmoked and hot smoked sausages, respectively (Fernandes et al, 2013).…”
Section: Proximate Compositionsupporting
confidence: 80%
“…Following the trend of this wild meat market, specialized farms commercialize in nature caiman meat and other manufactured products such as mortadella and sausage, which adds value to the species by-products (Fernandes et al 2014). The commercial farms promote economic development in the poorest villages of Pantanal (Brazil), and the regulation and inspection of slaughter also has an impact on human health by avoiding the consumption of wild meat without sanitary inspection.…”
Section: Introductionmentioning
confidence: 98%
“…Caiman meat is a great source of animal protein with high biological value and high digestibility in addition to a lower lipid content rich in polyunsaturated fatty acids than conventional meats, which is beneficial for human health (Canto et al, 2015;Hoffman & Cawthorn, 2013;Vicente-Neto et al, 2010). Moreover, caiman meat has a desirable taste and appearance, and flavor like between fish, chicken, and veal being well accepted by consumers (Canto et al, 2012;Fernandes et al, 2014;Hoffman & Cawthorn, 2012). Nevertheless, due to increasing demand of consumers by highquality food products, one of the main challenges of the meat industry is reduce the bacterial contamination, which occurs mainly during processing through contact of the carcass surface with their cavity and skin (Yang, Sadekuzzaman, & Ha, 2017).…”
Section: Introductionmentioning
confidence: 99%